High rate of solitary sentinel node metastases identification by fluorescence-guided lymphatic imaging in breast cancer - Hirche, Christoph (Journal of surgical oncology, 2012)
Background: The lymph node status was shown to be an important prognostic factor for breast cancer, but controversial issues remain. There has been increased focus on optimizing the visualization of lymph nodes for an accurate and selective approach to axillary lymph nodes. Fluorescence-guided lymphatic imaging is a potential candidate for further research on remaining controversies. Methods: Forty-seven patients were subject to injection of indocyanine green for navigation to the SLN based on fluorescent dye retention detection. In two groups, patients either received intended axillary lymph node dissection (ALND) and sentinel lymph node biopsy (SLNB) for superstaging or isolated SLNB for minimal-invasive staging. The prospective study was designed to evaluate the technical feasibility with focus on solitary positive SLN. Results Visualization of lymphatic vessels with bright fluorescence of the SLN was feasible in 46 of 47 patients. Eighteen of 19 nodal positive patients were correctly identified with a sensitivity of 94.7% in all patients after ALND. After immunohistochemistry, in 19 of 25 overall nodal positive patients (76%) the SLN was the only positive lymph node. Conclusion: Fluorescence-guided imaging using fluorescence retention detection allows transcutaneous navigation with a high rate of solitary positive SLN identification as an alternative technique for further research.